Healthcare managers' awareness: an operational definition built on a combination of hermeneutic phenomenology and survey research - Lai, Chi Quynh; Damart, Sébastien (HAL CCSD, 2018)
Managers’ awareness is a crucial predictor of successful coordination. The aim of the study is to develop an operational definition of the concept of awareness in healthcare management. We adopted a combination of hermeneutic phenomenology and survey research in a sequential approach. In the phenomenological qualitative phase, eight semi-structured interviews conducted with a diverse sample of health managers uncovered key proxies of the concept, including collecting the information, ensuring information verification, analyzing practices and integrative thinking and acting. We generated items clarifying indicators of each proxy to design the survey questionnaire and collected quantitative data from a sample of 144 respondents, covering a wide range of socio-demographics. The results of exploratory factors analysis reported a clear structure of four factors corresponding to the four identified proxies. The impacts of some socio-demographic characteristics on each proxy were also addressed.